Paradigma Hukum Perkawinan Kontemporer: Studi Atas Konsep Fikih Administratif Bidang Perkawinan - Shofiyulloh, Shofiyulloh; Rufaida, Arini (Isti`dal : Jurnal Studi Hukum Islam, 2024)
Many Muslims continue to practice marital law according to traditional jurisprudence, which leads to inconsistencies with laws and rules that uphold administrative norms. The significance of Muslims comprehending the framework of current Islamic marital law is underscored by this research. The practice of classical Islamic marital jurisprudence, which solely examines the legal procedure, has given way to a modern paradigm that also takes the process' effects into account. This is evident in issues pertaining to divorce, polygamy, marriage registration, age at marriage, and other administrative matters covered by statutory regulations but not previously addressed by classical jurisprudence guidelines. This study, which is part of the literature review, employs a qualitative approach to content analysis while examining different marriage administrations via the lenses of the contextual paradigm and maqa>s}id asy-syari>'ah. The purpose of this study is to highlight how Islamic marriage law is evolving in light of benefits and current trends. This study draws three conclusions. Firstly, the modern paradigm views marital law as so complicated that it requires specific regulation, including well-established administration. Second, it is believed that the administrative provisions of the legislation support the benefits of marriage by fulfilling the elements of maqa>s}id asy-syari>'ah and conforming to the contextual paradigm. Third, provided there are no obstacles in the way of the procedure or the associated expenses, Muslims can adopt marriage administration.